Pengaruh Transformasi Kampus Terhadap Motivasi Belajar Mahasiswa PAI Angkatan 2020: Studi: IAIN Bukittinggi Menjadi UIN Bukittinggi - Arif Aulia Rizki; Wedra Aprison (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research is motivated by the transformation of the IAIN Bukittinggi campus, which has now changed its status to UIN Bukittinggi. This change in status proves that UIN Bukittinggi wants to continue to promote and improve the quality of education. The change in status was felt more by students of the class of 2020 because when they became freshmen, the campus status was still IAIN, while mid-university it became UIN. Of course, with these changes, students' learning motivation should be better than before, especially PAI students, who are the foundation of UIN, because now the status of the campus is changing, everything should be improved better. Thus, this research focuses on the effect of campus transformation on the learning motivation of students from the PAI Class of 2020. This research is a quantitative correlational study. The population is 401 people and the sample consists of 55 people according to the Slovin formula. Data were collected using a questionnaire and analyzed using a simple linear regression test. The results of this study are that there is an influence of campus transformation on the learning motivation of the PAI student class of 2020, as shown by the results of the t > t table test, which is 3.167 > 1.674 and the size of the effect is 15 .92%